2008
DOI: 10.1037/a0013110
|View full text |Cite
|
Sign up to set email alerts
|

Development of proportional reasoning: Where young children go wrong.

Abstract: Previous studies have found that children have difficulty solving proportional reasoning problems involving discrete units until 10-to 12-years of age, but can solve parallel problems involving continuous quantities by 6-years of age. The present studies examine where children go wrong in processing proportions that involve discrete quantities. A computerized proportional equivalence choice task was administered to kindergartners through fourth-graders in Study 1, and to first-and third-graders in Study 2. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
242
6
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(278 citation statements)
references
References 73 publications
20
242
6
10
Order By: Relevance
“…This finding is particularly striking because adults should easily be able to ignore the segments and view the images as two continuous subsections, given that the similar colored elements are grouped together. The fact that discrete images favored counting not only for fractions but also for decimals is consistent with evidence (e.g., Boyer et al, 2008) that older children and adults are strongly predisposed to count whenever possible, whether or not counting is the optimal strategy. Counting does not align naturally with decimals, and estimation is less accurate than counting; hence, neither strategy is particularly well-suited for evaluating relations when decimals are paired with discrete images.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This finding is particularly striking because adults should easily be able to ignore the segments and view the images as two continuous subsections, given that the similar colored elements are grouped together. The fact that discrete images favored counting not only for fractions but also for decimals is consistent with evidence (e.g., Boyer et al, 2008) that older children and adults are strongly predisposed to count whenever possible, whether or not counting is the optimal strategy. Counting does not align naturally with decimals, and estimation is less accurate than counting; hence, neither strategy is particularly well-suited for evaluating relations when decimals are paired with discrete images.…”
Section: Discussionsupporting
confidence: 69%
“…Children must first learn the number words and map them onto counting procedures (Gelman & Gallistel, 1978;Rips, Bloomfield, & Asmuth, 2008). Counting provides more precision, and once children have mastered it, it seems to replace estimation as the dominant strategy (Boyer, Levine, & Huttenlocher, 2008;Mix, Levine, & Huttenlocher, 1999;Wynn, 1997).…”
Section: Processing Strategies For Quantitative Reasoningmentioning
confidence: 99%
“…Gray and Tall (1994) found that students who become proficient in arithmetic at an earlier age show greater ability to move back and forth flexibly between an arithmetic expression and the result of that expression. The difficulty in understanding a fraction as a relational expression may explain why young children appear to understand quantitative relations such as part-whole or proportions with visual displays (Goswami, 1989;Mix, Levine & Huttenlocher, 1999;Boyer, Levine, & Huttenlocher, 2008;Sophian, 2000), but not when they have to answer comparable questions with fraction notation (Ball & Wilson, 1996;Mack, 1995). For example, Ni and Zhou (2005) found that most children could answer the question, "How much is one third plus one third?"…”
Section: Implications For Teaching Rational Numbersmentioning
confidence: 99%
“…Children's apparent lack of competence could stem not from difficulties in reasoning about discrete quantities per se, but from the tendency to count when a task affords the opportunity (Jeong, Levine, & Huttenlocher, 2007;Boyer, Levine, & Huttenlocher, 2008). …”
Section: Multiplicative Transformationsmentioning
confidence: 99%